Prevalence and Correlates of Depression and Bipolar Disorder Among Patients Maintained on Methadone and Buprenorphine in Ukraine. - Morozova, Olga; Dvoriak, Vira; Dumchev, Kostyantyn; Machavariani, Eteri; Bromberg, Daniel J.; Dvoriak, Sergii; Altice, Frederick L. (International Journal of Mental Health & Addiction, 2025)
Psychiatric and substance use disorders frequently coexist and require co-management, yet little is known about the prevalence of psychiatric disorders among patients maintained on medications for opioid use disorder (MOUD) in Ukraine. We analyzed baseline data from a cluster-randomized trial of an integrated model of depression diagnosis and treatment among MOUD patients in Ukraine to determine prevalence and correlates of depression and bipolar disorder in this population. From a randomly selected sample of 1345 patients on MOUD at 12 sites in Ukraine, screening for moderate/severe depression (PHQ-9) and bipolar disorder (MDQ) yielded high prevalence of 50% (95% CI 42–58%) and 12% (95% CI 8–16%), respectively. Correlates of depression included recent drug injection, worse physical health, shorter duration on MOUD, higher methadone dosages, and stigma levels, being unmarried and having low trust in physicians. Bipolar disorder was correlated with alcohol use disorder and prior incarceration. The high burden of mental health disorders among patients prescribed MOUD in Ukraine calls for the urgent implementation of models to address co-occurring disorders, including those using integrated care strategies.